An Osgood Type Regularity Criterion for the 3D Boussinesq Equations. (11th March 2014) - Wu, Qiang; Hu, Lin; Liu, Guili
Abstract : We consider the three-dimensional Boussinesq equations, and obtain an Osgood type regularity criterion in terms of the velocity gradient.